A Review of Vector Filtering Schemes for Color Images Corrupted Y Impulse Noise - Rastislav Lukac; Stanislav Marchevsky (Communications - Scientific letters of the University of Zilina, 2001)
The development of modern communication technologies such as video phones, video conferencing systems, HDTV, Internet and digital television requires color image digital processing. Concerning the fact that color images represents vector-valued signals, the use of vector techniques is demanded. In the case of noise removing the problem is related with vector filters. On that reason, this paper is focused on reviewing the most frequently used vector filters for impulsenoise suppression in color images.